Financial Sector Assessment Program - Republic of Korea : Insurance Core Principles - World Bank (World Bank, Washington, DC, 2014)
This report is an assessment of Korea's compliance with International Association of Insurance Supervisors' Insurance Core Principles (ICPs), as adopted in October 2011. The review was carried out as part of the 2013 Financial Sector Assessment Program (FSAP) assessment of Korea, and was based on the regulatory framework in place, the supervisory practices employed, and other conditions as they existed in April 2013. The assessment was carried out by Craig Thorburn, Lead Insurance Specialist, Non-Bank Financial Institutions Group, Capital Markets Practice, World Bank. The assessment is based solely on the laws, regulations, and other supervisory requirements and practices that were in place at the time of assessment.